2023
DOI: 10.1097/corr.0000000000002578
|View full text |Cite
|
Sign up to set email alerts
|

Is Prolonged Use of Antibiotic Prophylaxis and Postoperative Antithrombotic and Antispasmodic Treatments Necessary After Digit Replantation or Revascularization?

Abstract: Background Ensuring the patency of repaired vessels is pivotal in improving the success rate of digit replantation. There is no consensus on how to best approach postoperative treatment for digit replantation. The influence of postoperative treatment on the risk of failure of revascularization or replantation remains unclear. Questions/purposes (1) Is there an increased risk of postoperative infection with early discontinuation of antibiotic prophylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…This study [1] reinforces the idea that the fundamental principles of digit replantation continue to guide outcome more than extended drug therapy and hospital stays. The next steps will involve fine-tuning what this study demonstrated; is 48 hours of antibiotics too much, or does it depend on the type of injury?…”
supporting
confidence: 79%
See 2 more Smart Citations
“…This study [1] reinforces the idea that the fundamental principles of digit replantation continue to guide outcome more than extended drug therapy and hospital stays. The next steps will involve fine-tuning what this study demonstrated; is 48 hours of antibiotics too much, or does it depend on the type of injury?…”
supporting
confidence: 79%
“…Realistically, any avulsion or crush injury will likely receive more medication and sharp injuries will be treated with less medication, but these are exactly the factors that could be stratified in an adequately powered randomized study. Although gathering these data may be difficult, the fact that the study center that published this CORR paper [1] performed more than 1000 replantations in under 4 years (although only 387 patients were included in this study after exclusions, they actually identified 1045) suggests that if we can organize several replantation centers to work together, a multicenter study on this topic is possible. Another practical approach may be to study the negative effects of medications to see whether we might minimize negative effects without sacrificing support of the replanted or revascularized digit.…”
Section: How Do We Get There?mentioning
confidence: 99%
See 1 more Smart Citation